Solid waste management: land application of agricultural & industrial by-products - Ishak, Che Fauziah (Universiti Putra Malaysia Press, 2018)
The generation of industrial wastes shows an increasing trend throughout the world including Malaysia. Recycling of these wastes or by-products on land is the most economically feasible. However, the presence of trace metal(loid)s is an issue of concern. Therefore, these by-products need to be assessed in terms of trace metal(loid)s content and their bioavailability before they can be land –applied. Bioavailability of trace metal(loid)s in the soil system can be transferred to the food chain via plant uptake and leaching to ground water or transported via surface runoffs to water bodies. Thus, the ultimate goal of remediation is to reduce the transfer of trace metal(loid)s to the food chain. One of the remediation method recommended is the in-situ immobilization technique. In this technique, the remediation of trace metal(loids-rich or contaminated soils will be through manipulating their bioavailability by using a range of soil amendments such as liming materials, organic materials or biosolids, phosphate compounds and metal oxides (Ferich materials). The soil chemical processes exploited to immobilize metal(loid)s in-situ are the adsorption and precipitation processes.